Molecular epidemiology of Brucella abortus in Shandong, China: high-resolution insights from combined MLVA-16 and core genome SNP analysis - Huangfu, Chanjuan; Ma, Xiujun; Fan, Junjie; Han, Kuo; Liu, Ti; Kou, Zengqiang; Li, Yan (Frontiers in Microbiology, 2025)
IntroductionThe recent identification of Brucella abortus in human clinical samples from Shandong, China, highlights an ongoing zoonotic threat.MethodsWe characterized 12 B. abortus strains isolated from human patients since 2021 using a combination of conventional biotyping, Multiple Locus Variable-number Tandem Repeat Analysis (MLVA), and core-genome SNP (cgSNP) analysis.ResultsEpidemiological data indicated that infections primarily occurred in middle-aged men with occupational livestock exposure. Molecular typing revealed biovar 3 as the predominant type (91.7%), dominated by MLVA-8 genotype 36 and its corresponding MLVA-11 genotype 72 (66.7%). MLVA-16 distinguished 12 unique genotypes. The phylogeny based on cgSNP classified the strains into clades C1 (11 bv. 3 strains) and C2 (one bv. 1 strain). Within clade C1, nine strains in subclade C1-III exhibited ≤119 SNP differences, eight of which formed a local clonal transmission chain (≤52 SNPs) and shared MLVA-11 genotype 72. Subclade C1-I contained two strains with novel genotypes resulting from variations at the Bruce18 and Bruce43 loci. The sole C2 strain differed by only 3 SNPs from the A19 vaccine strain, suggesting a potential vaccine-related origin. Genetic links were also identified with strains from other Chinese provinces, among them Heilongjiang and Inner Mongolia, as well as from several countries, including Mongolia and Russia.DiscussionThese findings revealed a complex epidemiological pattern in Shandong, primarily characterized by local transmission chains with occasional external introductions, provided a scientific basis for targeted brucellosis control strategies.